Banking reform in China: Driven by international standards and Chinese specifics - Zdenek Kudrna (Transformation, Integration and Globalization Economic Research (TIGER), 2007)
This paper reviews the progress of banking reforms in China over the last five years. The stated goal of reform is to 'transform major banks into internationally competitive joint-stock commercial banks with appropriate corporate governance structures, adequate capital, stringent internal controls, safe and sound business operations, quality services as well as desirable profitability.' The reform strategy relies on three pillars - extensive publicly financed bailouts, implementation of the international best practices in bank governance and regulation and listing of major banks at the Hong Kong stock exchange. This strategy has been successful in stabilizing the three major banks. However, our review of academic and commercial research indicates that there is no evidence that the stabilization is sustainable. Prudential indicators of the largest banks are comparable to international averages, but this is an outcome of large bail outs and ongoing credit boom rather than fundamental change in banker's incentives. Reforms of bank governance and regulatory framework need more time to proliferate throughout the banking and regulatory hierarchies. However, time alone would not solve the problem as the reform design retains important departures from international standards. These standards are implemented in a selective manner; those aspects that help to concentrate key powers in the center are implemented rather vigorously, whereas principles that require independence of banks' boards and regulators are ignored. Thus the largest Chinese banks remain under the firm state control and can be used as development policy tools for the better or the worse.
Keywords: G21; G28; P34; 330; China; banks; reform; international standards; Bank; Bankenreform; China